ANALISIS EFEKTIVITAS TUGAS POKOK DAN FUNGSI PENGELOLA BARANG DALAM PENATAUSAHAAN BARANG MILIK NEGARA DI SEKOLAH TINGGI METEOROLOGI KLIMATOLOGI DAN GEOFISIKA - Wibowo, Shindyko; Giyanto, Bambang; Munawar, Munawar; Darmawan, Yahya; Habibi, Naufal Ilham (Media Mahardhika, 2024)
This study aims to measure the effectiveness of asset managers in administering State-Owned Assets (BMN) at the Meteorology, Climatology, and Geophysics School (STMKG), as identified in the 2017-2018 Operational Audit Report. The research employs a mixed-method approach, utilizing both qualitative and quantitative methods, with data collected through Likert-scale questionnaires and in-depth interviews with six respondents. Data analysis was performed using Smart PLS software. The findings indicate that while the asset managers at STMKG meet the minimum educational qualifications of a Diploma III, they lack the necessary certification in BMN Management Technical Substantive Training (DTSS). However, the managers demonstrate strong competencies in technical, cognitive, and social aspects, which significantly support their roles. The study highlights deficiencies in the reporting and disposal processes of BMN and emphasizes the need for formal training to enhance the effectiveness of BMN management.